Effect of negative pressure wound therapy applied in the emergency center on postoperative infection rates in patients with orthopedic open wounds - Eriten, Semih; İzci, Vedat and Menekşe, Serdar (The European Research Journal, 2025)
Objectives: This study aimed to evaluate the effect of Negative Pressure Wound Therapy (NPWT) applied in the emergency department on postoperative infection rates in patients with orthopedic open injuries. Methods: This prospective randomized controlled study included 80 patients who presented with orthopedic open injuries. Patients were divided into two groups: NPWT group (n=40) and control group receiving standard wound care (n=40). An average pressure of 125±25 mmHg was applied in the NPWT group. Demographic characteristics, wound characteristics, infection rates, length of hospital stay, and treatment outcomes were evaluated. Results: The infection rate in the NPWT group (7.5%) was significantly lower compared to the control group (25.0%) (P=0.034). The NPWT group showed significantly lower numbers of surgical debridement (1.3±0.6 vs 2.1±0.8, P=0.008), shorter antibiotic use duration (10±3 vs 14±4 days, P=0.003), and shorter hospital stay (8±2 vs 14±3 days, P<0.001). Primary closure rate was significantly higher in the NPWT group (70%) compared to the control group (30%) (P=0.002). Conclusions: NPWT applied in the emergency department significantly reduces postoperative infection rates, accelerates wound healing, and shortens hospital stay in orthopedic open injuries. These findings suggest that NPWT may have an important role in the early treatment protocol of open injuries.